2008
DOI: 10.1016/j.bioorg.2008.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid-binding site environments of serum vitamin D-binding protein and albumin are different

Abstract: Vitamin D-binding protein (DBP) and albumin (ALB) are abundant serum proteins and both possess high-affinity binding for saturated and unsaturated fatty acids. However, certain differences exist. We surmised that in cases where serum albumin level is low, DBP presumably can act as a transporter of fatty acids. To explore this possibility we synthesized several alkylating derivatives of 14 Cpalmitic acid to probe the fatty acid binding pockets of DBP and ALB. We observed that N-ethyl-5-phenylisooxazolium-3′-sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Final methanolysis of the O ‐acetate groups, followed by hydrogenolysis of the Z‐group, gave the free chito‐oligosaccharide (CO) 30 23a. After chromatography on silica gel, this compound was subjected to selective N ‐acylation using an excess of palmitoyl chloride 31 37 by heating (40 °C) in the presence of NaHCO 3 . The target compound, Myc (C16:0, S) 3S , was purified by chromatography on silica gel (ethyl acetate/methanol/water, 5:2:1 as eluent) and gel filtration through a Sephadex G‐25 column.…”
Section: Resultsmentioning
confidence: 99%
“…Final methanolysis of the O ‐acetate groups, followed by hydrogenolysis of the Z‐group, gave the free chito‐oligosaccharide (CO) 30 23a. After chromatography on silica gel, this compound was subjected to selective N ‐acylation using an excess of palmitoyl chloride 31 37 by heating (40 °C) in the presence of NaHCO 3 . The target compound, Myc (C16:0, S) 3S , was purified by chromatography on silica gel (ethyl acetate/methanol/water, 5:2:1 as eluent) and gel filtration through a Sephadex G‐25 column.…”
Section: Resultsmentioning
confidence: 99%
“…palmitic acid) [87]. These results point towards a different binding and transport of various fatty acids between DBP and albumin [85].…”
Section: The Fatty Acid-binding Site Environment Of Vitamin D Bindingmentioning
confidence: 97%
“…The fatty acidbinding pockets of DBP and albumin have a different chemical/electronic environment. The fatty acid-binding site of DBP can only accommodate a polar and zwitterionic head group of palmitic acid, whereas a hydrophobic and hydrophilic head group at the carboxy-terminus are tolerated [85]. The molar ratio of fatty acids bound to albumin (1.8) is also much higher in comparison with DBP (0.4).…”
Section: The Fatty Acid-binding Site Environment Of Vitamin D Bindingmentioning
confidence: 97%
See 1 more Smart Citation
“…Saturated and unsaturated free fatty acids (FFA) can bind DBP and ALB, although cross‐linking studies with derivatives of palmitic acid indicated differences in the FFA binding domains of ALB and DBP . Addition of unsaturated fatty acids reduced DBP affinity for 25D and 1,25D slightly, whereas saturated fatty acids did not .…”
Section: Biological Functions Of Dbpmentioning
confidence: 99%